WORDS GOLD - GOLD - GOLD IN THE RUSSIAN POETIC COLOR AND METAPHORICAL PALETTE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article deals with the semantic features of Russian adjectives golden, golden,golden and their functioning in Russian poetry. It is argued that their metaphorical meaning changedin different time periods and with different authors (Alexander Pushkin, Anna Akhmatova, BellaAkhmadullina, Bulat Okudzhava, Vladimir Vysotsky). The purpose of the article is to conduct acomparative analysis of the use of these words in Russian poetry of the 19th and 20th centuries. It isargued that over time, the main metaphorical shifts in the use of the analyzed words are associatedboth with the individual style of the author and with the general turn towards a pragmatic society inthe second half of the 20th century. Thus, the analysis of the indirect meanings of these adjectivesreveals the differences in the Russian linguistic picture of the world in different periods of time.
Keywords: semantics; metaphor; poetry; semantic shift; color term.